The Significance of Interreligious Harmony in the Context of Islam and Indonesian Pluralism - Rizki Yana; Nurjaya Nurjaya; Hudallah Hudallah (Penerbit Hellow Pustaka, 2025)
This study aims to explore the meaning of interreligious harmony within the contexts of Islam and Indonesian society. It employs a literature review method, analyzing relevant books and previous studies on interfaith relations. The findings reveal that interreligious harmony in Indonesia is rooted in values of tolerance, mutual respect, and shared humanity, which are also emphasized in Islamic teachings. Islam encourages peaceful coexistence with followers of other religions and highlights the importance of understanding and dialogue. The discussion underscores the role of Islam in promoting peace and social cohesion in a diverse society like Indonesia. Furthermore, the study indicates that strengthening interreligious harmony can reinforce national unity and social stability. This research contributes to a deeper understanding of the role of Islam in supporting religious pluralism and interfaith dialogue in the Indonesian context.